2022
DOI: 10.1093/g3journal/jkac127
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of sex-biased gene expression in the spotted-wing Drosophila, Drosophila suzukii (Matsumura)

Abstract: Sexual dimorphism occurs widely throughout insects and has profound influences on evolutionary path. Sex-biased genes are considered to account for most of phenotypic differences between sexes. In order to explore the sex-biased genes potentially associated with sexual dimorphism and sexual development in Drosophila suzukii, a major devastating and invasive crop pest, we conducted whole-organism transcriptome profiling and sex-biased gene expression analysis on adults of both sexes. We identified transcripts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…D. suzukii were fed on an artificial diet consisting of cornmeal, yeast, soy flour, maltose syrup and agar at Hunan Normal University (Changsha, China) and cultured at 25 °C under 12 h light: 12 h dark photoperiod [ 98 ]. Methyl 4-hydroxybenzoate was used as a preservative to prevent the overgrowth of fungi and bacteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…D. suzukii were fed on an artificial diet consisting of cornmeal, yeast, soy flour, maltose syrup and agar at Hunan Normal University (Changsha, China) and cultured at 25 °C under 12 h light: 12 h dark photoperiod [ 98 ]. Methyl 4-hydroxybenzoate was used as a preservative to prevent the overgrowth of fungi and bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting P -values were corrected using the Benjamini and Hochberg’s method for managing the false discovery rate (FDR). Genes with an corrected P -value < 0.05 found by DESeq2 were appointed as differentially expressed genes (DEGs) [ 98 ]. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of DEGs was performed by Phyper based on Hypergeometric test [ 104 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of various insect genomes and RNA sequences facilitates a genome-based approach to identifying biological targets for insect control. Since the genome of D. suzukii was published [ 7 ], a few case studies analyzing the functional transcriptome of its antennae were reported [ 8 , 9 , 10 ]. A comprehensive genome study was recently achieved by the long-read sequencing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Generally, phenotypic differences between males and females are caused by a series of differentially expressed genes, thus, identification of differentially expressed genes in sexes is crucial for insect behavior and physiological analysis. 13 For parasitoid wasps, it is essential to identify the sex-differences because only female wasps are capable of parasitism, however, there are currently few reports of the differences between the female and male parasitoid wasps on the molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%